2008
DOI: 10.12968/jowc.2008.17.4.28839
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro examination of the antioxidant and anti-inflammatory properties of buckwheat honey

Abstract: As buckwheat honey was most effective in reducing ROS levels, it was selected for use in wound-healing products. The major antioxidant properties in buckwheat honey derive from its phenolic constituents, which are present in relatively large amounts. Its phenolic compounds may also exert antibacterial activity, whereas its low pH and high free acid content may assist wound healing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
77
0
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(87 citation statements)
references
References 28 publications
4
77
0
6
Order By: Relevance
“…It has been hypothesized that honey's healing effect on wounds of rodents and humans may in part be due to its antioxidant, antibacterial and anti-inflammatory effects (Van den Berg et al, 2008), based on the effect of honey or parts of its constituents on mediators of inflammation.…”
Section: Resultsmentioning
confidence: 99%
“…It has been hypothesized that honey's healing effect on wounds of rodents and humans may in part be due to its antioxidant, antibacterial and anti-inflammatory effects (Van den Berg et al, 2008), based on the effect of honey or parts of its constituents on mediators of inflammation.…”
Section: Resultsmentioning
confidence: 99%
“…Leong et al (2011) reported that honey exhibited potent and dose-dependent reduction of human neutrophil superoxide anion production in vitro. Other groups also described a scavenger activity of honey on O ·− 2 using the xanthinexanthine oxidase system (Henriques et al 2006;Van den Berg et al 2008). Honey was also found to decrease the luminol-enhanced chemiluminescence in opsonized zymosan-stimulated whole blood and isolated leucocytes (Mesaik et al 2008).…”
Section: Discussionmentioning
confidence: 97%
“…Buckwheat hull extract was shown to be effective for protecting biological systems against various oxidative stresses in vitro, and to have antioxidant activity in vivo [71].Buckwheat honey samples were tested for inhibition of reactive oxygen species (ROS) production by activated human PMNs, antioxidant activity (scavenging of superoxide anion in a cell-free system) and inhibition of human complement (reducing levels of ROS by limiting formation of complement factors that attract and stimulate PMNs). Most honey samples were shown to be active inhibitors of reactive oxygen species [72]. The culture and buckwheat dough matrix was evaluated with respect to total phenolic content and antioxidant potential.…”
Section: Iii-pharmacological Effectsmentioning
confidence: 99%